Empiric radioiodine for hyperthyroidism: Outcomes, prescribing patterns, and its place in the modern era of theranostics. (11th May 2022) - Boehm, Emma; Kao, Yung Hsiang; Lai, Jeffrey; Wraight, Paul R.; Sivaratnam, Dinesh A.
Abstract: Background: The modern era of radioiodine (I‐131) theranostics for metastatic differentiated thyroid cancer requires us to rationalize the role of traditional empiric prescription in nonmalignant thyroid disease. We currently practice empiric I‐131 prescription for treatment of hyperthyroidism. This study aims to assess outcomes after treatment of hyperthyroidism by empiric I‐131 prescription at our centre, evaluate factors that impact on outcomes and prescribing practice, and gain insight into whether there is a place for theranostically‐guided prescription in hyperthyroidism. Patients and Methods: A retrospective review was undertaken of all patients with Graves' disease, toxic multinodular goitre (MNG) and toxic adenoma treated with I‐131 between 2016 and 2021. Associations between clinical or scintigraphic variables and remission (euthyroid or hypothyroid) or persistence of hyperthyroidism at follow‐up were performed using standard t test as well as Pearson's product correlation. Results: Of 146 patients with a mean follow‐up of 13.6 months, 80.8% achieved remission of hyperthyroidism. This was highest in toxic nodules (90.1%), compared with Graves' disease (73.8%) and toxic MNG (75.5%). In patients with Graves' disease, higher administered activity was associated with remission ( p = .035). There was a weak inverse correlation between the Tc‐99m pertechnetate uptake vs prescribed activity in Graves' disease ( r = −0.33; p = .009). Only one patient (0.7%) had an I‐131 induced flare of thyrotoxicosis. Conclusion: Traditional empiric I‐131 prescription is a safe and effective treatment of hyperthyroidism and suitable for most patients. However, there may be a role for personalized I‐131 prescription by theranostic guidance in selected patients with high thyroid hyperactivity.